2021
DOI: 10.1007/s10933-021-00175-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of climate change and industrialization on Lake Bolshoe Toko, eastern Siberia

Abstract: Industrialization in the Northern Hemisphere has led to warming and pollution of natural ecosystems. We used paleolimnological methods to explore whether recent climate change and/or pollution had affected a very remote lake ecosystem, i.e. one without nearby direct human influence. We compared sediment samples that date from before and after the onset of industrialization in the mid-nineteenth century, from four short cores taken at water depths between 12.1 and 68.3 m in Lake Bolshoe Toko, eastern Siberia. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 69 publications
3
15
0
Order By: Relevance
“…Further methodological uncertainty can arise through oversimplified estimation of dry bulk density (DBD) from empirical equations of DBD and carbon content where discrete, volumetric measurements do not exist (Avnimelech et al, 2001;Kastowski et al, 2011) as well as varied approaches used for the measurement of sample carbon contents (elemental analyser vs. loss on ignition (LOI)) (Munroe and Brencher, 2019). Limitations associated with radiocarbon dating of Arctic glacial lakes due to the absence of appreciable amounts of datable organic material, particularly during glacial phases as well as the reworking of old organic carbon present within catchment sediments that can be brought to the lake basin through permafrost and glacial processes during warm and cold phases respectively, can additionally lead to uncertainty with regards to sediment ages and hence reconstructed accumulation rates (Abbott and Stafford, 1996;Björck and Wohlfarth 2002;Oswald et al, 2005). Despite this, the calculated OCARs and pools for Lake Rauchuagytgyn are largely agreeable with multiple studies from northern regions and reinforce the reliability, applicability and novelty of the presented results.…”
Section: Regional and Local Controls On Carbon Accumulation And Methodological Limitationsmentioning
confidence: 99%
“…Further methodological uncertainty can arise through oversimplified estimation of dry bulk density (DBD) from empirical equations of DBD and carbon content where discrete, volumetric measurements do not exist (Avnimelech et al, 2001;Kastowski et al, 2011) as well as varied approaches used for the measurement of sample carbon contents (elemental analyser vs. loss on ignition (LOI)) (Munroe and Brencher, 2019). Limitations associated with radiocarbon dating of Arctic glacial lakes due to the absence of appreciable amounts of datable organic material, particularly during glacial phases as well as the reworking of old organic carbon present within catchment sediments that can be brought to the lake basin through permafrost and glacial processes during warm and cold phases respectively, can additionally lead to uncertainty with regards to sediment ages and hence reconstructed accumulation rates (Abbott and Stafford, 1996;Björck and Wohlfarth 2002;Oswald et al, 2005). Despite this, the calculated OCARs and pools for Lake Rauchuagytgyn are largely agreeable with multiple studies from northern regions and reinforce the reliability, applicability and novelty of the presented results.…”
Section: Regional and Local Controls On Carbon Accumulation And Methodological Limitationsmentioning
confidence: 99%
“…sults, an age-depth model was computed using Bacon v.2.4.3 (Blaauw and Christen, 2011;package "rbacon";Blaauw et al, 2020), combining Pb/Cs and adjusted 14 C ages of all bulk samples calibrated with the IntCal20 14 C calibration curve (Reimer et al, 2020).…”
Section: Lithology and Age Datingmentioning
confidence: 99%
“…30 and 40 km distance, respectively). It has also been shown that even very remote lake systems in Yakutia have been affected by human activity from industrialization (Biskaborn et al, 2021). Yakutia has been populated by humans since at least ca.…”
Section: Human Activitymentioning
confidence: 99%
“…Today, the sedimentary basin of Lake Bolshoe Toko is 15 km long and 8 km wide, situated at the northern foot of the Stanovoy Mountains representing most of the lake's catchment (Biskaborn et al, 2021). The Bolshoe Toko basin forms a surficial landform on the southeastern Siberian Platform, which is built up of cratonic basement rocks of Precambrian age and overlain by Paleozoic to Mesozoic sedimentary rock strata and Quaternary cover sediments, in places with intercalated volcanic rock units (Nikishin et al, 2010;Barnet and Steiner, 2021).…”
Section: Study Sitementioning
confidence: 99%
“…Although the Siberian region is generally regarded as being underrepresented in paleoenvironmental research (Sundqvist et al, 2014;Mckay et al, 2018;Kaufman et al, 2020), there is an ever-expanding interest in the area due to expected environmental changes and associated strong socioenvironmental implications (Amap, 2017). In particular, remote Arctic lakes in permafrost regions represent pristine earlywarning systems of environmental change, as they rapidly respond to climatic perturbations and changes in geoecological boundary conditions in their catchments (Subetto et al, 2017;Biskaborn et al, 2021;Nazarova L. B. et al, 2021). In terms of environmental sustainability, they still provide an infinite resource of uncontaminated fresh water, which make them unique compared to lake systems in the highly populated mid-latitude areas (Serreze et al, 2006).…”
Section: Introductionmentioning
confidence: 99%